2017
DOI: 10.1111/acps.12698
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral cytokine and chemokine alterations in depression: a meta‐analysis of 82 studies

Abstract: Objective To conduct a systematic review and meta‐analysis of studies that measured cytokine and chemokine levels in individuals with major depressive disorder (MDD) compared to healthy controls (HCs). Method The PubMed/MEDLINE, EMBASE, and PsycINFO databases were searched up until May 30, 2016. Effect sizes were estimated with random‐effects models. Result Eighty‐two studies comprising 3212 participants with MDD and 2798 HCs met inclusion criteria. Peripheral levels of interleukin‐6 (IL‐6), tumor necrosis fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
697
10
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,103 publications
(830 citation statements)
references
References 74 publications
41
697
10
13
Order By: Relevance
“…Another meta‐analysis of inflammatory biomarkers in patients with MDD undergoing antidepressant treatment reported no decrease in the elevated baseline TNFα level. In that report, however, there was a decrease in the TNFα level in responders compared with nonresponders (Köhler et al., 2017). …”
Section: Discussionmentioning
confidence: 99%
“…Another meta‐analysis of inflammatory biomarkers in patients with MDD undergoing antidepressant treatment reported no decrease in the elevated baseline TNFα level. In that report, however, there was a decrease in the TNFα level in responders compared with nonresponders (Köhler et al., 2017). …”
Section: Discussionmentioning
confidence: 99%
“…In regard to depression/anxiety, current evidence suggests that elevated expression of the pro-inflammatory cytokine inter-leukin-6 (IL-6) in the periphery and downregulation of Ras-related C3 botulinum toxin substrate-1 (Rac-1) expression in the nucleus accumbens (NAc) in the brain both play key roles in desensitizing the brain reward system, thereby increasing sensitivity to stress-mediated depression/anxiety phenotypes. 3538 As highlighted by red arrows in Figure 3B, our integrative analysis revealed that IL-6 expression is significantly inhibited by select biologically available phenolic metabolites derived from BDPP treatment, particularly 3-(3′-hydroxyphenyl)propionic acid (3-HPP), dihydrocaffeic acid (DHCA), 3′- O -Me-epicatechin-5- O -glucuronide (Me-EC-Gln), and quercetin-3- O -glucuronide (Q-Gln). Moreover, Rac-1 expression is significantly induced by malvidin-glucoside, another BDPP metabolite.…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have presented data supporting similar outcomes. In a Norwegian study among schizophrenic ( n = 344) and nonschizophrenic groups ( n = 308), depression was related to LDL and TC levels, while in another study it was shown that depression was associated with elevated levels of several inflammatory cytokines [29-31]. In contrast to our results, Shah et al [32] reported that there was no association of HbA 1c , blood pressure, and LDL cholesterol with depression in adults with type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%